Exploring the Impact of Sand Play on the Psychomotor Development of One-Year-Old Children - Pratama, Fajar Shidiq (Jurnal Psikologi Terapan, 2024)
This study aims to analyze the effect of sand play on the psychomotor development of 1-year-old children. Playing in the sand is believed to stimulate gross and fine motor skills through multisensory activities that involve object manipulation and body movements. With a qualitative approach, this study uses a direct observation method on 30 1-year-old children while playing in the sand. Activities such as digging and moving sand are evaluated for gross motor, while pinching and shaping sand is evaluated for fine motor. The results showed that sand play contributed significantly to children's motor coordination, concentration, and sensory exploration. These findings support the theory of child development which emphasizes the importance of multisensory stimulation in supporting motor growth. In addition to the physical benefits, the study also found that playing sand supports children's social, emotional, and cognitive development, such as interaction skills, logical thinking, and creativity. This study recommends parents and educators to utilize sand play as part of child development stimulation by paying attention to safety and hygiene aspects.